STRATEGI PEDAGANG DALAM MENAWARKAN BARANG DAGANGANNYA : ANALISIS TINDAK TUTUR JUAL BELI DI PASAR GROSIR SUMATERA BARAT - Silviana Masran (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This writing is aimed at describing the linguistic phenomenon of speech act in offering. The objective of the writing is to identify the strategies of the merchants in offering their trade in green grocery in West Sumatra. The data are any utterances containing offering uttered by the merchants involved in the process of selling the trade in a traditional green grocery in Alahan Panjang, Solok Regency, West Sumatera. In collecting data, the observational method with note-taking, recording, and interviewing is used. The data are analyzed by referential and pragmatic identity method. The analysis is related to the concept proposed by Searle (1979). The result of analysis is descriptively done. Having analyzed the data, it is found that there are four strategies of the merchants in offering their trade. They are (1) questioning; (2) offering; (3) giving information; and (4) asking.